Data from: Genetic architecture of survival and fitness-related traits in two populations of Atlantic salmon - Houde, Aimee Lee S.; Wilson, Chris C.; Neff, Bryan D. (2020)
The additive genetic effects of traits can be used to predict evolutionary trajectories, such as responses to selection. Non-additive genetic and maternal environmental effects can also change evolutionary trajectories and influence phenotypes, but these later effects have received less attention by researchers. We partitioned the phenotypic variance of survival and fitness-related traits into additive genetic, non- additive genetic, and maternal environmental effects using a full-factorial breeding design within two allopatric populations of Atlantic salmon (Salmo salar). Maternal environmental effects were large at early life stages, but decreased during development, with non-additive genetic effects being most significant at later juvenile stages (alevin and fry). Non- additive genetic effects were also, on average, larger than additive genetic effects. The populations, generally, did not differ in the trait values or inferred genetic architecture of the traits. Any differences between the populations for trait values could be explained by maternal environmental effects. We discuss if the similarities in architectures of these populations is the result of natural selection across a common juvenile environment. Houde_heredityEarly life-history survival and fitness-related traits. Growing degree days information.